(untitled) (Journal of Oriental Studies, 2021)
Literature is the writer’s ink manifestation of the art of expression. Fiction is the most important form of art. In the flow of communication, the synthesis of culture and literature has always been present. The influence of the concept of enlightenment in literature on culture is the subject of this article. The concept of enlightenment ushered in a period of cultural modernization in society, which was accompanied by advances in scientific, metaphysical, and social thought. The Enlightenment is regarded as one of the most pivotal times in Western and Eastern history. It was a time of intellectual movement, of liberation from darkness, of liberation from oppression by revolution, and of a shift in the social category based on rationalism and free thought. The aim of this article is to compare the harmony in the artistic heritage of Indian and Kazakh authors, who are great representatives of national culture in the dialogue of civilizations, to examine the manifestation of the concept of enlightenment in society in literature, and to demonstrate that this time brought significant social changes. Keywords: enlightenment period, enlightenment idea, literature, revolution, intellectual movement, modernization, society, realism.